Kajian Ilmiah Terhadap sinema Kebangsaan dan ciri-ciri Identiti dalam filem Malaysia - Khairudin, K. (Universiti Malaysia Sarawak, UNIMAS, 2007)
"Laga" the purpose of the research is to permeate meaning and type's national cinema with showing reality of people's life. A few researchers looking national cinema and finding the similarities of this type. This research also analyzing the films such as Sepet, Spinning Gasing and Jogho to support this theory